Caracterización física-química de arcillas en los centros poblados: Padre Cocha y Santo Tomás, Iquitos 2023 - Torres García, Jack Gabriel (2024)
In Iquitos, the predominant sediments are fine sand and clay, without rocky outcrops or coarse aggregates. The research focuses on characterizing the physical-chemical properties of the clays from Padre Cocha and Santo Tomás in 2023. This quantitative, comparative and non-experimental research reveals significant differences in the properties of the clays, useful for various industrial and artisanal applications. The clays of these populated centers, derived from feldspars, present the following physical properties: Granulometry at mesh No. 200 is 56.76% and 98.08%; Sand is 43.11% and 1.56%; Limo is 38.64% and 49.01%; Clay is 18.25% and 49.43%; Humidity is 29.21% and 60.78%; Specific gravity is 2.658 and 2.602; Liquid limit is 30 and 51; Plastic limit is 15 and 22; Plastic index is 15 and 29, respectively. Regarding the chemical properties, the following values were found: Silicon Dioxide (SiO2) is 59.11%; Calcium Oxide (CaO) is 2.34%; Aluminum Trioxide (Al2O3) is 20.84%; Iron Trioxide (Fe2O3) is 13.36%; Potassium Oxide (K2O) is 1.89%; Magnesium Oxide (MgO) is 0.37%; Phosphorus Pentoxide (P2O5) is 0.06%; Copper Oxide (CuO) is 0.02%; Sulfur Trioxide (SO3) is 0.01%; Zinc Oxide (ZnO) is 0.28%; Manganese Oxide (MnO) is 0.04%, respectively. Clays have distinctive physical-chemical characteristics that can be used in various industries, from ceramics to pharmaceuticals and cosmetics.